Asem, Sawo, Kelapa, dan Masyarakat Kota Serang - Tustiantina, Diana (UI Scholars Hub, 2017)
Representation of community identity can be displayed through the diversity of culture and traditions. The result of a growing culture one of which is the culinary community. Representation identity is shown through herbs and materials used in processing. This study tries to assess and explain the meaning through symbols and markings on the tree represents Identity society through semiotic approach Danesi and Perron (1999, 94-95), which is done through three stages: (1) denotative, (2) connotative, and (3 ) annotation. Primary data in this study is the meaning of the coconut trees, Tamarind trees and Sapodilla trees. The collection of data and information is done by library research, interviews and focus group discussions. The method used in this research is qualitative descriptive which researchers describe the findings of data and data processing. The results showed that tamarind, coconut and sapodilla be a representation of the community’s identity when it is used as a flavouring and food ingredients typical culinary of Serang city, as well as unique souvenirs of Serang city. Tamarind, coconut and sapodilla interpreted as a spice, food, and souvenirs that are typical for the Serang city. The third symbol is the representation of the identity of the Serang city as peculiar, cultural factors, and bound historical background. Representation of the identity of the Serang city can provide representation through three trees, the tamarind tree, coconut tree and sapodilla tree.